Michael Handelsman: estudioso, archivero y crítico de la prosa literaria escrita por mujeres en Ecuador (Tributo) - Ortega Caicedo, Alicia del Rosario (2019)
This paper intends to recognize and highlight the outstanding input made by critic Michael Handelsman in his study on narrative (both essayistic and fictional) written by women in Ecuador. It is important to highlight the scope of a work committed to place women’s writing in the cultural and political sphere and show its impact on the public and social scene, in the horizon of its production, circulation and reception possibilities. Handelsman’s writings (where he studies essays, novels, short stories and magazines written by Ecuadorian women) are approached with the purpose of observing his reading strategies, which lead him to conceive Literature as a struggle scenario for female writers: a space of self-representation, resistance and production of knowledge, in tension with a system of patriarchal values. Above all, this paper is a tribute to the task continually performed by Michael Handelsman for some decades, with generosity and lucidity, in the search and construction of the corpus that constitutes its object of study. It is a corpus scattered through libraries, archives, magazines, anthologies, which Handelsman has located, attended to, taken care of, systematized, periodized, valued, placed for debate, generated affiliations therewith, always insisting on the existence and scope of the valuable –and sometimes forgotten narrative tradition– produced in Ecuador by female writers.